2007
DOI: 10.1299/jmmp.1.114
|View full text |Cite
|
Sign up to set email alerts
|

Crystal Plasticity Analysis of Non-uniform Deformation in Symmetric Type Bicrystals under Tensile Load and Formation of Geometrically Necessary Dislocation Bands

Abstract: Slip deformation in symmetric type bicrystal models subjected to tensile load is analyzed by a finite element crystal plasticity analysis code and accumulation of geometrically necessary dislocations (GNDs) is studied in detail. Uniform deformation was expected to take place because mutual constraint of crystal grains through the grain boundary plane does not occur in symmetric type bicrystals, but, some results of the analysis show non-uniform deformation and the high density of GNDs accumulated in the form o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2007
2007
2018
2018

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 11 publications
0
7
0
Order By: Relevance
“…In the previous study, we observed that nonuniform deformation took place with the accumulation of highdensity GN dislocations in the form of bands in symmetric bicrystal models depending on boundary conditions and the combination of the crystal orientation (5), (6) , and that the GN dislocation structure exhibited nonuniform deformation behavior. In this study, we discuss the effect of asymmetric GN dislocation structure formation in bicrystal models with a tilted angle grain boundary on subsequent deformation behavior.…”
Section: Effect Of Initial Crystal Orientation On Gn Dislocation Stmentioning
confidence: 93%
See 3 more Smart Citations
“…In the previous study, we observed that nonuniform deformation took place with the accumulation of highdensity GN dislocations in the form of bands in symmetric bicrystal models depending on boundary conditions and the combination of the crystal orientation (5), (6) , and that the GN dislocation structure exhibited nonuniform deformation behavior. In this study, we discuss the effect of asymmetric GN dislocation structure formation in bicrystal models with a tilted angle grain boundary on subsequent deformation behavior.…”
Section: Effect Of Initial Crystal Orientation On Gn Dislocation Stmentioning
confidence: 93%
“…Grain boundary planes are perpendicular to the x -y planes of the model, which uniformly divide the model into 3 200 finite elements. The continuity requirements of strain components across the grain boundary plane between grains 1 and 2 are given by the following relationships (5), (6) :…”
Section: Basic Equationmentioning
confidence: 99%
See 2 more Smart Citations
“…We have performed crystal plasticity analysis of tensile deformation in compatible-type bicrystals satisfy the requirement in which the effects of the elastic incompatibility stress and the plastic stain incompatibility does not work (1) (5) , and stated in a previous study that non-uniform deformation with GN dislocation structure correspond to the kink bands and secondary slip bands (6) were formed in the crystal grains depended on the boundary condition of external loading (7) and the initial crystal orientation (8) , even if the grain boundary effect, in which had been thought to be the main cause of the non-uniform deformation, was removed from analysis model. It was described to cause these phenomena by mutually constrained the shape change of the crystal grain due to the slip deformation in the active slip systems by the boundary condition of external load and the grain boundary (6)(7)(8) .…”
Section: Introductionmentioning
confidence: 99%